COMPARING THE GUT METABOLOMIC PROFILES IN HISPANIC AND NON-HISPANIC PEDIATRIC ULCERATIVE COLITIS PATIENTS. (22nd January 2022) - Hosseini, Parastou Khalessi; Michail, Sonia
Abstract: BACKGROUND: Diagnosis of ulcerative colitis (UC), a subgroup of inflammatory bowel disease (IBD), is frequently overlooked among the Hispanic population. Although previously thought to impact predominantly white populations, epidemiological studies have shown an increased incidence of UC among Hispanics. Other studies have also noted variations in disease phenotype when comparing Hispanic UC patients to non-Hispanic patients. These variations could be linked to differences in the gut microbiome and shifts in the metabolomic profile. This study aims to compare the profiles of Hispanic UC patients to those of non-Hispanic whites. METHODS: Participants aged 7-21 with mild to moderate UC were enrolled at Children's Hospital of Los Angeles. Eighteen Hispanic and forty non-Hispanic patients were included in this analysis. Metabolite profiling yielded 230 known metabolites. Independent sample T-tests were used to identify significant differences (p<0.05) in metabolites between Hispanic and non-Hispanic UC samples. The average for each metabolite was calculated in Hispanic, non-Hispanic, and healthy patients. Averages were then compared and used to define metabolites as enhanced or diminished. RESULTS: 66 metabolites were found to be significantly different between Hispanic and non-Hispanic UC patients. When comparing the profiles of Hispanic to that of non-Hispanic patients, 2 metabolites were enhanced and 64 were diminished. The two enhanced metabolites included 1-monostearin and 1-monopalmitin. Figure 1 depicts the top 10 most diminished metabolites in Hispanic patients compared to non-Hispanic patients. These 10 metabolites were amino acids, amino acid degradation products, and one polyol compound. DISCUSSION: This study found a significant difference in the metabolomic profiles of Hispanic UC patients compared to non-Hispanics. This difference could suggest a relationship between ethnicity and the gut's metabolomic profile. Most notably, Hispanic patients were found to have diminished levels of nearly all significantly different metabolites when compared to non-Hispanic patients. This includes protective fatty acids, amino acids, and amino acid degradation byproducts. Increased deficits of protective anti-inflammatory mediators can be linked to increased risk of severe disease among Hispanic UC patients. These findings support the need for therapeutics targeting specific metabolite deficiencies within Hispanic UC patients.